Bostad Först - mer än ett hem: En kvalitativ studie om deltagarnas upplevelser och personalens beskrivningar av insatsens olika delar - Vidberg,Anton; Berggren,Victoria (2026)
This study focuses on examining how participants and staff describe the Housing First initiative, focusing on the experiences of the central parts of the Housing First initiative. To investigate this, we chose a qualitative method. We interviewed six people. Two staff members who work within Housing First and four participants who are involved in Housing First initiatives. With the help of semi-structured interviews, we gained a broader understanding of how the Housing First initiative is experienced and also practiced in the organization. The results and analysis showed that the implementation of Housing First in the municipality we investigated has yielded good results from the perspective of the participants and the staff. The Housing first-participants' view of having their own accommodation is strongly associated with a sense of safety and security. With the help of the staff's attitude and support efforts, the participants' sense of autonomy increases, and in this way, the emotional significance and motivation to participate in everyday life also increase. Both staff and participants pointed out that the meeting place was an important aspect of the Housing First initiative howeve,r the open hours are limited. Therefore, it could be in the interest of Housing First projects to develop this part of the initiative.
Keywords: housing First; homelessness; the KASAM theory; recognition theory